2012
DOI: 10.1002/jcb.24177
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of feeder free anchorage independent cultures of ES and iPS cells by retinol/vitamin A

Abstract: Pluripotent embryonic stem (ES) cells derived from mammalian blastocyst and the adult fibroblast derived induced pluripotent stem (iPS cells) exhibit complete potential to form cells representing all the primary germ layers such as mesoderm, endoderm and ectoderm. These cells are usually co-cultured with mouse embryonic fibroblast feeders to prevent spontaneous differentiation. Feeder free cultures can provide substantial advantage to improve the efficiency and consistency of the culture conditions. In these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Retinol treatment of mouse ESCs and induced pluripotent stem cells (iPS) cells resulted in the elimination of differentiated cells leaving only pure population of undifferentiated cells [54] suggesting that the differentiated cells may have been eliminated via terminal differentiation due to their ability to metabolize retinol into retinoic acid. The undifferentiated characteristics of these cells were confirmed by generating chimeric animals via injection of cells into mouse blastocysts.…”
Section: Purity Of Stem Cell Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinol treatment of mouse ESCs and induced pluripotent stem cells (iPS) cells resulted in the elimination of differentiated cells leaving only pure population of undifferentiated cells [54] suggesting that the differentiated cells may have been eliminated via terminal differentiation due to their ability to metabolize retinol into retinoic acid. The undifferentiated characteristics of these cells were confirmed by generating chimeric animals via injection of cells into mouse blastocysts.…”
Section: Purity Of Stem Cell Populationmentioning
confidence: 99%
“…The undifferentiated characteristics of these cells were confirmed by generating chimeric animals via injection of cells into mouse blastocysts. The microinjection of cells resulted in the chimeric animals that exhibited high percentage of ESC contribution accompanied by germ line transmission of coat color of the ESCs [54]. …”
Section: Purity Of Stem Cell Populationmentioning
confidence: 99%
“…Similarly, it is necessary to develop culture tools that are indispensable for maintaining the undifferentiated state of hiPSC cultures. As a good writing tool provides “paper and pencil to write a beautiful letter” and “an eraser to be able to correct mistakes,” hiPSC culture requires “good substrate and nutrient medium” to control the occurrence of deviating cells, with many studies having previously investigated hiPSC‐culture media and substrates . However, something equivalent to an eraser in this context does not yet exist, and removal technology involving not only the hiPSC‐nutrient medium and substrate, but also the unprecedented concept of removing deviating cells will be indispensable in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Recent studies showed that it is possible to maintain hiPSC pluripotency and self-renewal through artificial manipulation, and the exogenous expression of molecules associated with epigenetic regulation revealed that this can be achieved through addition or withdrawal of certain cytokines and/or growth factors or by changing the transcriptional activity of genes. [23][24][25][26][27][28][29][30][31] Methods based on culturing undifferentiated hiPSCs in monolayers have also been reported, although they present significant limitations. Specifically, hiPSC cultures are very difficult to handle, as they have a tendency to change state easily upon each passage or operation, which can lead to unintentional spontaneous differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Human embryonic stem (hES) cells can be maintained in an undifferentiated state by highly skilled researchers and engineers [1, 2]. In addition to skill development, reagents and automated instruments (e.g., kinase inhibitors [3, 4] and time‐lapse analyses [2, 5]) have been developed to maintain the undifferentiated potencies of stem cells.…”
Section: Introductionmentioning
confidence: 99%